2022
DOI: 10.1002/pbc.29558
|View full text |Cite
|
Sign up to set email alerts
|

De novo TP53 germline activating mutations in two patients with the phenotype mimicking Diamond–Blackfan anemia

Abstract: Diamond–Blackfan anemia (DBA) is an inherited bone marrow failure syndrome, associated with mutations in ribosomal protein (RP) genes. Growing data on mutations in non‐RP genes in patients with DBA‐like phenotype became available over recent years. We describe two patients with the phenotype of DBA (onset of macrocytic anemia within the first year of life, paucity of erythroid precursors in bone marrow) and germline de novo variants in the TP53 gene. Both patients became transfusion independent, probably due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…A deficiency in the transcription factor MYSM1 in mice or humans impairs RP expression and causes TP53-dependent bone marrow failure ( 58 , 59 ). Most importantly, germline activating TP53 mutations cause a clinical phenotype of DBA ( 60 , 61 ). The current work supports these previous studies and provides new experimental approaches to investigate mechanisms of TP53 activation resulting from RP deficiency and the resultant functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A deficiency in the transcription factor MYSM1 in mice or humans impairs RP expression and causes TP53-dependent bone marrow failure ( 58 , 59 ). Most importantly, germline activating TP53 mutations cause a clinical phenotype of DBA ( 60 , 61 ). The current work supports these previous studies and provides new experimental approaches to investigate mechanisms of TP53 activation resulting from RP deficiency and the resultant functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, defects in telomere maintenance or in the FA DNA repair pathway were long known to cause p53 activation, but our results indicated that, conversely, increased p53 activity might affect telomere function and DNA repair, hence defining positive feedback loops that might contribute to the clinical overlap between DC and FA [26]. Interestingly, the clinical traits of humans with a germline activating TP53 mutation also revealed features of DBA [38][39][40], a bone marrow failure syndrome also partially similar to DC or FA, and mutations in DBA-causal genes are also known to cause p53 activation [9,[66][67][68][69][70]. In that case, however, evidence for a positive feedback loop was not established, because no DBA-causal gene had been reported to be downregulated by p53.…”
Section: Food For Thought: Modeling P53 In a Circuitry Of Genes Assoc...mentioning
confidence: 65%
“…These phenotypes were suggestive of a DBA-like syndrome with additional features more common in DC [38]. Additional patients with similar TP53 mutations were later confirmed to present DBA-like features, but could exhibit normal telomere length [39,40].…”
Section: The Plot Thickens: Germline P53 Activation Underlies Feature...mentioning
confidence: 76%
“…They also demonstrated that high cell cycle speed was required during MEPs fate decision, and erythroid progenitors have significantly more proliferation than megakaryocyte-committed progenitors by scRNA-seq analysis [ 54 ]. In addition, individuals with gain-of-function mutations in exon 10 of p53 gene were reported to have DBA-like syndromes between DBA and dyskeratosis congenita [ 55 ]. GATA1 was also demonstrated to have impact on p53 inhibition [ 56 ].…”
Section: Introductionmentioning
confidence: 99%